2017
DOI: 10.1038/s41467-017-00458-y
|View full text |Cite
|
Sign up to set email alerts
|

Above-threshold scattering about a Feshbach resonance for ultracold atoms in an optical collider

Abstract: Ultracold atomic gases have realized numerous paradigms of condensed matter physics, where control over interactions has crucially been afforded by tunable Feshbach resonances. So far, the characterization of these Feshbach resonances has almost exclusively relied on experiments in the threshold regime near zero energy. Here, we use a laser-based collider to probe a narrow magnetic Feshbach resonance of rubidium above threshold. By measuring the overall atomic loss from colliding clouds as a function of magnet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…Over the past decade a laser-based collider for ultracold atoms has been constructed at the University of Otago (Rakonjac et al 2012;Thomas et al 2016;Horvath et al 2017;Thomas et al 2018;. This optical collider makes use of the fact that, generally, polarisable neutral particles can be confined and manipulated by laser light (Ashkin 1997).…”
Section: Collision Experiments At Otagomentioning
confidence: 99%
“…Over the past decade a laser-based collider for ultracold atoms has been constructed at the University of Otago (Rakonjac et al 2012;Thomas et al 2016;Horvath et al 2017;Thomas et al 2018;. This optical collider makes use of the fact that, generally, polarisable neutral particles can be confined and manipulated by laser light (Ashkin 1997).…”
Section: Collision Experiments At Otagomentioning
confidence: 99%
“…When two atoms collide their interaction is complex, leading to a wide range of possible outcomes. The result of the collision strongly depends upon experimental parameters such as the internal atomic states, the collisional energy, and external electromagnetic fields 1 . Modern atomic physics experiments exploit the richness of these atomic interactions to engineer systems for a remarkable variety of purposes, including quantum information processing 2 and quantum simulation 3,4 .…”
Section: Introductionmentioning
confidence: 99%
“…3f, the resonance profile becomes noticeably broader as the collision energy increases, and the signal contrast becomes weaker. However, we have found that the narrow resonance imprints itself on the spatial profile of the atomic clouds, and we can use this imprint to accurately determine the resonance position over a range of collision energies even when the observed loss is within the noise level of our measurements [25].…”
Section: Measuring Inelastic Scattering Near a Feshbach Resonancementioning
confidence: 99%
“…As a second demonstration of our collider, we considered a narrow Feshbach resonance of 87 Rb centered at 9.045 G (at threshold [24]) between the internal states |2, 0 and |1, 1 for which we measured inelastic scattering as the resonance was magnetically tuned to lie above threshold [25]. Elastic scattering for this system is weak, producing faint scattering halos, but the inelastic loss into undetected and higher kinetic energy states is significant.…”
Section: Measuring Inelastic Scattering Near a Feshbach Resonancementioning
confidence: 99%